Association of self-reported sedentary time with insulin resistance among Korean adults without diabetes mellitus: a cross-sectional study - Kyeong Seok Kim; Seong Jun Kim; Seonggwan Kim; Dong-Woo Choi; Yeong Jun Ju; Eun-Cheol Park (BMC, 2018)
Abstract Background A more sedentary lifestyle can result in insulin resistance. However, few research studies have assessed the association between insulin resistance and sedentary lifestyle in Asian populations. Therefore, this study aimed to investigate the association of sedentary time with insulin resistance. In addition, we also investigate the moderate effect of employment status, moderate-to-vigorous physical activity (MVPA), and body mass index (BMI) in this association. Methods Data from 2573 individuals who participated in the 2015 Korean National Health and Nutrition Examination Survey were analyzed. Sedentary time was measured using self-administered questionnaires, and IR data were estimated using the homeostasis model assessment-insulin resistance index (HOMA-IR). Adjusted odds ratio (OR) and 95% confidence intervals (CIs) from a multivariable logistic regression model were generated for all participants. Subgroup analysis was only performed between sedentary time and HOMA-IR stratified by employment status, because moderate effects were not significant in the tests for interaction for MVPA and BMI. For all analyses, the individuals were categorized as having high or normal HOMA-IR values (> 1.6 and ≤ 1.6, respectively). Results A HOMA-IR > 1.6 was observed in 40.3% of the sedentary time Q1 (low) group (< 5.0 h/day), 41.4% of the sedentary time Q2 (middle-low) group, 44.2% of the sedentary time Q3 (middle-high) group, and 48.4% of the sedentary time Q4 (high) group (≥10.0 h/day). When the low level sedentary time group was used as the reference group, the high level sedentary time group was significantly associated with high IR value (HOMA-IR > 1.6) (OR = 1.40, 95% CI: 1.060-1.838). However, this association was not significant across the other sedentary time groups. Moreover, participants reporting a high sedentary time and were employed had 1.67 times the odds of having a high IR value (HOMA-IR > 1.6) compared to those who reported having a low sedentary time and were employed (OR = 1.67, 95% CI: 1.184-2.344). In the unemployed participants, sedentary time was not associated with IR. Conclusions High sedentary time (≥10.0 h/day) was associated with elevated HOMA-IR among Korean adults without diabetes mellitus. Furthermore, the association between high sedentary time and HOMA-IR values was more pronounced in the employed population.